Free will : an historical and philosophical introduction - Dilman, Ilham (Routledge, 1999)
What is the place of human free will in our lives if all our actions are the result of some other cause? Does our possessing unconscious beliefs or desires make us less free? Is our free will necessarily restricted if we do not choose our own beliefs? The debate between free will and its opposing doctrine, determinism, is one of the key issues in philosophy. Free Will: An historical and philosophical introduction provides a comprehensive introduction to this highly important question and examines the contributions made by sixteen of the most outstanding thinkers from the time of early Greece to the twentieth century: Homer, Sophocles, Plato, Aristotle, St. Augustine, St. Thomas Aquinas, Descartes, Spinoza, Sartre, Weil, Wittgenstein, Moore.